A novel suture method to place and adjust peripheral nerve catheters2. (27th February 2015) - Rothe, C.; Steen‐Hansen, C.; Madsen, M. H.; Lundstrøm, L. H.; Heimburger, R.; Jensen, K. E.; Lange, K. H. W.
Summary We have developed a peripheral nerve catheter, attached to a needle, which works like an adjustable suture. We used in‐plane ultrasound guidance to place 45 catheters close to the femoral, saphenous, sciatic and distal tibial nerves in cadaver legs. We displaced catheters after their initial placement and then attempted to return them to their original positions. We used ultrasound to evaluate the initial and secondary catheter placements and the spread of injectate around the nerves. In 10 cases, we confirmed catheter position by magnetic resonance imaging. We judged 43/45 initial placements successful and 42/43 secondary placements successful by ultrasound, confirmed in 10/10 cases by magnetic resonance imaging.